Zakat dan Pajak dalam Pandangan Masdar Farid Mas'udi - Tri Nurhayati (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2009)
Masdar Farid Mas'udi is intended to maintain the Islamic social construction by discussing zakat historically. He defined zakat as a tax concept that combined the two concepts from the government and Islam. He offered some concepts on interpreting that dualism.